Spatiotemporal Analysis of Land Use and Cover Dynamics in Protected Areas of the Brazilian Cerrado - Mariele R. Torgeski; Emerson M. de Carvalho; Alex M. dos Santos; Ana P. Lemke; Claudemir A. G. Fioratti; Mauricio Stefanes; Sandro M. Silva; Rosilda M. Mussury (Scientifica)
The Brazilian Cerrado, renowned as the most biodiverse savanna, is characterized by its pronounced climatic seasonality, diverse vegetation mosaic, and distinct topographic variations. Natural protected areas (NPA) within this biome play a pivotal role in safeguarding both biodiversity and natural resources. The objective of this study is to analyze the dynamic shifts in land use and land cover across seven NPA and their corresponding buffer zones (BZs) within a Cerrado region situated in Central-West Brazil. This research encompasses a comprehensive multitemporal analysis of satellite imagery spanning the period from 1985 to 2018 utilizing a geographic information system (GIS). The variability in land use and land cover classes is considerably more constrained within the NPA than BZs. The Templo dos Pilares Municipal Natural Park exhibits substantial expanses of preserved vegetation, while the Nascentes do Rio Taquari State Park demonstrates an extensive prevalence of pasturelands. The NPA exhibit coherent patterns of land cover transformation within their respective BZs. However, alterations in the landscape within the BZs offer insights into potential forthcoming challenges to the NPA. Escalated land use within the surrounding matrix of protected areas presents a formidable obstacle to biodiversity conservation, owing to extraneous pressures. A comprehensive understanding of the spatiotemporal distribution of land use and land cover within safeguarded Cerrado regions contributes substantively to the augmentation of management, preservation, and conservation endeavors over time.